Proposta de um espaço educador virtual para o CECFAU – Centro de Conservação de Fauna Do Estado de São Paulo - Bueno, Giovanna Cristine de Sena (Universidade Federal de São Carlos, 2024)
This study addresses the importance of environmental education in the context of biodiversity conservation, with a focus on endangered species maintained by the Wildlife Conservation Center of the State of São Paulo (CECFau). The main objective was to understand the perspectives and experiences of the CECFau technical team in order to develop a Virtual Educational Space, a tool aimed at raising public awareness about wildlife conservation by integrating key conservation concepts. To achieve this, semi-structured interviews were conducted with CECFau technicians to identify essential themes for shaping the educational space, emphasizing the need to increase public knowledge about the existence and goals of CECFau, as highlighted by the interviewees. The Virtual Educational Space serves as a resource to increase CECFau's visibility by utilizing virtual, audiovisual, and interactive tools, and by developing interactive materials that provide access to the center’s technical-scientific knowledge while encouraging community involvement. Activities include a 3D virtual tour, a video, and a game. The virtual tour offers an immersive experience of the habitats and introduces the animals of CECFau. The video clarifies concepts related to ex-situ and in-situ conservation in an integrated manner, while the game, using a "conflict theater" methodology, promotes the development of concepts related to wildlife conservation through the interactive and dynamic resolution of problem-based scenarios. Thus, the project has demonstrated its potential for CECFau’s educational actions, which can foster greater integration between science, community, and conservation policies.
Proposal for a virtual educational space for CECFAU – Wildlife Conservation Center of the State of São Paulo
Keywords: Educação Ambiental; Conservação ex-situ; Espaço Educador Virtual; Espécies em Extinção; CECFau; Biodiversidade; Environmental Education; Ex-situ Conservation; Virtual Educational Space; Endangered Species; Biodiversity; CIENCIAS BIOLOGICAS::BIOLOGIA GERAL; CIENCIAS BIOLOGICAS; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE AREAS SILVESTRES